Enhancement-Mode High-Frequency InAlGaN/GaN MIS-HEMT Fabricated by Implementing Oxygen-Based Digital Etching on the Quaternary Layer. (1st August 2022) - Tsai, Ping-Yu; Nguyen, Hoang-Tan-Ngoc; Nagarajan, Venkatesan; Lin, Chun-Hsiung; Dee, Chang-Fu; Chen, Shih-Chen; Kuo, Hao-Chung; Lee, Ching-Ting; Chang, Edward Yi
Abstract : A high frequency enhancement mode quaternary InAlGaN/GaN MIS-HEMT with recessed gate (Lg = 150 nm) processed using an oxygen-based digital etching technique is presented. The digital etching was performed by cyclic ICP oxygen treatment to oxidize InAlGaN barrier and HCl wet etching to remove the oxidized layer. In this study, we have demonstrated that the threshold voltage can be adjusted in a wide-range from depletion mode to enhancement mode with a nanometer scale gate for high frequency InAlGaN/GaN MIS-HEMT using the digital etching technique. In addition, the etch rate can be controlled from 0.7 nm/cycle to 3.6 nm cycle −1 with RF bias power changing from 0 W to 40 W with high flexibility in etching rate. The post-etching surface roughness was around 0.12 nm regardless of the ICP oxidation voltage. The enhancement-mode InAlGaN quaternary GaN HEMT with maximum drain current of 955 mA mm −1, gm −1 peak of 440 mS mm −1, Vth of 0.2 V, and ft /fmax of 45/59 GHz were achieved using the digital etching for the gate recess structure.